Molecular physiopathology of obesity-related diseases: multi-organ integration by GRK2. (20th October 2015) - Lucas, Elisa; Cruces-Sande, Marta; Briones, Ana M.; Salaices, Mercedes; Mayor, Federico; Murga, Cristina; Vila-Bedmar, Rocio
Abstract: Obesity is a worldwide problem that has reached epidemic proportions both in developed and developing countries. The excessive accumulation of fat poses a risk to health since it favours the development of metabolic alterations including insulin resistance and tissue inflammation, which further contribute to the progress of the complex pathological scenario observed in the obese. In this review we put together the different outcomes of fat accumulation and insulin resistance in the main insulin-responsive tissues, and discuss the role of some of the key molecular routes that control disease progression both in an organ-specific and also in a more systemic manner. In particular, we focus on the importance of studying the integrated regulation of different organs and pathways that contribute to the global pathophysiology of this condition with a specific emphasis on the role of emerging key molecular nodes such as the G protein-coupled receptor kinase 2 (GRK2) signalling hub.